2016
DOI: 10.3389/fncel.2016.00099
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Translocation of High Mobility Group Box 1 Facilitates LIM Kinase 2-Mediated Programmed Necrotic Neuronal Death

Abstract: High mobility group box 1 (HMGB1) acts a signaling molecule regulating a wide range of inflammatory responses in extracellular space. HMGB1 also stabilizes nucleosomal structure and facilitates gene transcription. Under pathophysiological conditions, nuclear HMGB1 is immediately transported to the cytoplasm through chromosome region maintenance 1 (CRM1). Recently, we have reported that up-regulation of LIM kinase 2 (LIMK2) expression induces HMGB1 export from neuronal nuclei during status epilepticus (SE)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…The merged pictures of Drp1 with HMGB1 not only supported the colocalization of HMGB1 with Drp1, but also suggested the functional role of surface binding HMGB1 in mitochondrial fission. Interestingly, a recent study using a pilocarpine-induced status epilepticus model suggested that nuclear HMGB1 translocation and the subsequent mitochondrial import might deteriorate programmed necrotic neuronal death [19]. In addition, mitochondrial DNA (mtDNA) has been reported to be released from injured cells as DAMPs (damage associated molecular patterns), and HMGB1 has high affinity to DNA [20].…”
Section: Discussionmentioning
confidence: 99%
“…The merged pictures of Drp1 with HMGB1 not only supported the colocalization of HMGB1 with Drp1, but also suggested the functional role of surface binding HMGB1 in mitochondrial fission. Interestingly, a recent study using a pilocarpine-induced status epilepticus model suggested that nuclear HMGB1 translocation and the subsequent mitochondrial import might deteriorate programmed necrotic neuronal death [19]. In addition, mitochondrial DNA (mtDNA) has been reported to be released from injured cells as DAMPs (damage associated molecular patterns), and HMGB1 has high affinity to DNA [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astrocytes and microglia can respond to HMGB1 by producing pro-inflammatory conditions, which is suggested to play an important role in neuroinflammation in neurodegenerative diseases [51–53]. HMGB1 is an important pro-inflammatory cytokine, but it has also been implicated in a necrotic cell death response [54, 55]. Following acute injuries, such as ischemic brain insults, HMGB1 is translocated out of the nucleus and appears to play a role in necrosis or necroptosis (programed cell death in response to injury) [55].…”
Section: Discussionmentioning
confidence: 99%
“…Dentate hilar neurons and CA1-3 pyramidal cell are extremely vulnerable to insults, while dentate granule cells are resistant ( Ordy et al, 1993 ; Mathern et al, 1995 ; Wittner et al, 2001 ; Kim et al, 2011 ; Ryu et al, 2011 ). Interestingly, hippocampal neurons also show the distinct cell death patterns in the different hippocampal regions following SE: CA1 pyramidal cell death is necrotic rather than apoptotic ( Kim et al, 2014 ; Ko et al, 2015 ; Hyun et al, 2016 ), but PV cells is caspase-3 dependent apoptotic ( Kang et al, 2006 ). Recently, we have reported that the impaired mitochondrial fission induces programmed necrosis in CA1 pyramidal cells following SE ( Kim et al, 2014 ; Ko et al, 2015 ; Hyun et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hippocampal neurons also show the distinct cell death patterns in the different hippocampal regions following SE: CA1 pyramidal cell death is necrotic rather than apoptotic ( Kim et al, 2014 ; Ko et al, 2015 ; Hyun et al, 2016 ), but PV cells is caspase-3 dependent apoptotic ( Kang et al, 2006 ). Recently, we have reported that the impaired mitochondrial fission induces programmed necrosis in CA1 pyramidal cells following SE ( Kim et al, 2014 ; Ko et al, 2015 ; Hyun et al, 2016 ). Unlike CA1 neurons, the present study reveals that SE resulted in PV cell loss through excessive mitochondrial fragmentation, and Mdivi-1 effectively ameliorated SE-induced PV cell loss.…”
Section: Discussionmentioning
confidence: 99%